The evidence for using tenofovir disoproxil fumarate plus lamivudine as a nucleoside analogue backbone for the treatment of HIV - Laura Waters; Viraj Mehta; Jaideep Gogtay; Marta Boffito (Elsevier, 2021)
This article evaluates the evidence supporting use of the tenofovir disoproxil fumarate (TDF) plus lamivudine (3​TC) combination as a dual nucleoside backbone within a triple drug antiretroviral regimen. Key trials that assess the relative efficacy, safety and resistance profile of 3​TC and emtricitabine (FTC) are discussed. Clinical use of 3​TC and FTC with two tenofovir prodrugs -TDF and tenofovir alafenamide (TAF) - is presented. Recommendations from various international guidelines for the construction of triple and emerging dual regimens are summarised. In conclusion, data suggest the therapeutic equivalence of 3​TC and FTC, especially when 3​TC is combined with TDF.